2016
DOI: 10.1097/md.0000000000003862
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of surgical treatments for lower urinary tract symptoms/benign prostatic hyperplasia on male erectile function

Abstract: Lower urinary tract symptoms (LUTS)/benign prostatic hyperplasia (BPH) is common in adult men and can impair erectile function (EF). It was believed surgical treatments for this illness can improve EF due to the relief of LUTS while they were also reported harmed EF as heating or injury effect. Current network meta-analysis aimed to elucidate this discrepancy.Randomized controlled trials (RCTs) were identified. Direct comparisons were conducted by STATA and network meta-analysis was conducted by Generate Mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 66 publications
2
19
1
1
Order By: Relevance
“…The authors believed, however, that the reason for such decrease is the neurovascular bundles damage, because of the generated monopolar current passed in close proximity to the prostatic capsule [ 20 ]. This theory was in part confirmed by Li et al [ 21 ], as they indicated in their meta-analysis a predominantly small EF decrease during a short-term follow-up. However, at a follow-up of 12 months after TURP, the average EF values returned to normal and did not differ from those recorded preoperatively, especially in patients presenting with an initially high EF value [ 21 ].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The authors believed, however, that the reason for such decrease is the neurovascular bundles damage, because of the generated monopolar current passed in close proximity to the prostatic capsule [ 20 ]. This theory was in part confirmed by Li et al [ 21 ], as they indicated in their meta-analysis a predominantly small EF decrease during a short-term follow-up. However, at a follow-up of 12 months after TURP, the average EF values returned to normal and did not differ from those recorded preoperatively, especially in patients presenting with an initially high EF value [ 21 ].…”
Section: Discussionsupporting
confidence: 65%
“…This theory was in part confirmed by Li et al [ 21 ], as they indicated in their meta-analysis a predominantly small EF decrease during a short-term follow-up. However, at a follow-up of 12 months after TURP, the average EF values returned to normal and did not differ from those recorded preoperatively, especially in patients presenting with an initially high EF value [ 21 ].…”
Section: Discussionsupporting
confidence: 65%
“…Incidence of new-onset REj rates were reported at 30–67.1% with an additional 5.4% risk of developing painful ejaculation after PVP [44, 46, 47]. Although single institutional studies have shown no detrimental effects of PVP on erectile function, a recent meta-analysis by Li et al demonstrated that of the nine BPH procedures analyzed, PVP was the only one to negatively impact short-term postoperative erectile function [46, 48, 49]. It is also important to note that studies utilizing higher laser energy levels have a higher propensity to developing sexual dysfunction [19].…”
Section: Bph Surgeries and Sexual Dysfunctionmentioning
confidence: 99%
“…Some researchers reported that drug administration or surgical intervention improves symptoms of lower urinary tract syndrome as well as ED 35. Additionally, Li et al reported that 14% of all patients who received surgical intervention had some resolution of ED symptoms; however, the authors also reported that 16% of patients experienced worsening symptoms postoperatively 6. On the other hand, another study indicated that nerve injury-related electroporation heat may result in postoperative ED 7…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, the larger the weight of the prostate part to be removed, the higher the risk of ED-related nerve damage. Recent studies of the association between TURP and postoperative ED focused on different surgical intervention methods, the difference between drug administration and surgical intervention, and the effects of bipolar and unipolar electroporation 6,911. However, few studies have examined the relation between the resected prostate weight and postoperative, new-onset ED.…”
Section: Introductionmentioning
confidence: 99%